2004
DOI: 10.1143/jjap.43.5006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ultrafast Crystallization in As-Deposited Ge2Sb2Te5 Films

Abstract: Femtosecond laser-induced ultrafast crystallization in 80 nm as-deposited Ge 2 Sb 2 Te 5 films has been investigated by timeresolved microscopy. With an average fluence of approximately 10 mJ/cm 2 , a transient nonequilibrium state of the excited material was formed within 2 ps. The results can be interpreted as an electronically induced nonthermal phase transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…28 Previous theoretical studies estimate that about 11% valence electron excitation is required to induce lattice instability in covalently bonded silicon and gallium arsenide. 21,29,30 The crystalline structure of Sb 2 Te 3 , as well as other Ge−Sb−Te alloys, is stabilized by a network of resonant bonds. It is still to be determined, the exact electronic and ionic processes leading to the destabilization of Sb 2 Te 3 crystalline structure and resulting nonthermal amorphization by femtosecond laser photoexcitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Previous theoretical studies estimate that about 11% valence electron excitation is required to induce lattice instability in covalently bonded silicon and gallium arsenide. 21,29,30 The crystalline structure of Sb 2 Te 3 , as well as other Ge−Sb−Te alloys, is stabilized by a network of resonant bonds. It is still to be determined, the exact electronic and ionic processes leading to the destabilization of Sb 2 Te 3 crystalline structure and resulting nonthermal amorphization by femtosecond laser photoexcitation.…”
mentioning
confidence: 99%
“…loss of long-range order without involving a melt-quench process. Time-resolved optical measurements and theoretical studies reported ultrafast subpicosecond amorphization induced by femtosecond lasers in different materials. The ultrafast time-scale and low energy involved in the nonthermal amorphization process are highly sought after for energy efficient and high transfer rate devices . Previous theoretical studies estimate that about 11% valence electron excitation is required to induce lattice instability in covalently bonded silicon and gallium arsenide. ,, The crystalline structure of Sb 2 Te 3 , as well as other Ge–Sb–Te alloys, is stabilized by a network of resonant bonds. It is still to be determined, the exact electronic and ionic processes leading to the destabilization of Sb 2 Te 3 crystalline structure and resulting nonthermal amorphization by femtosecond laser photoexcitation.…”
mentioning
confidence: 99%
“…5) However, details of the PC process have not been elucidated yet. Although Kolobov et al have clarified from detailed X-ray absorption fine structure (XAFS) and X-ray absorption near-edge structure (XANES) analyses that the PC process is not a real phase transition from the amorphous to crystalline states, but rather a change between two crystalline phases, they did not refer to the lack of long-range order in the X-ray diffraction (XRD) patterns in the ''amorphous state''.…”
mentioning
confidence: 99%
“…The observation of the crystallization process in PC materials has been performed by a reflectivity change or by tracing a thermal analysis curve during the amorphous-tocrystalline transition, as well as by X-ray structural analysis 3,4) and time-resolved microscopy. 5) However, details of the PC process have not been elucidated yet. Although Kolobov et al have clarified from detailed X-ray absorption fine structure (XAFS) and X-ray absorption near-edge structure (XANES) analyses that the PC process is not a real phase transition from the amorphous to crystalline states, but rather a change between two crystalline phases, they did not refer to the lack of long-range order in the X-ray diffraction (XRD) patterns in the ''amorphous state''.…”
mentioning
confidence: 99%